Potential of Lycium barbarum polysaccharide for the control of glucose and lipid metabolism disorders: a review - Rongrong Huang; Enhui Wu; Xiangliang Deng (International Journal of Food Properties, 2022)
Glucose and lipid metabolism disorders (GLMD) are typically characterized by the metabolic disturbance of glucose and lipid. Clinically, GLMD includes diabetes, hyperlipidemia, obesity and nonalcoholic fatty liver disease. Studies found that Lycium barbarum polysaccharides (LBP) have activities of hypoglycemic, lowering blood lipids, anti-inflammatory, antioxidant and antitumor. Among them, the effects of LBP on improving insulin sensitivity, regulating blood lipids and reducing blood glucose have attracted much attention. This paper reviews the beneficial effects of LBP on controlling glucose and lipid metabolism diseases, so as to provide evidence for the potential use of LBP as a healthy food material for the control of metabolic diseases.